Rheumatic manifestations of inflammatory bowel diseases: A study from the Middle East. Issue 9 (September 2018) - Hammoudeh, Mohammed; Elsayed, Eman; Al-Kaabi, Saad; Sharma, Manik; Elbadri, Mohamed; Chandra, Prem; Abu Nahia, Niveen; Hammoudeh, Samer
Objective: To examine the prevalence of rheumatic manifestations among patients with inflammatory bowel disease (IBD). Methods: This prospective study enrolled patients with IBD in whom the diagnosis and extent of IBD were confirmed by colonoscopy and histopathology. Patients were interviewed and examined by a rheumatologist. A complete rheumatological examination, X-rays of the lumbosacral and sacroiliac joints and HLA-B27 blood tests were performed. Results: A total of 127 adult patients were recruited: 46 (36.2%) with Crohn's disease (CD) and 81 (63.8%) with ulcerative colitis (UC). Rheumatic manifestations of any type were present in 57.5% (73 of 127 patients) with no significant differences between CD and UC. Peripheral manifestations were present in 43.3% (55 of 127 patients), four patients (3.1%) had axial arthritis alone and 14 patients (11.0%) had both types. Among those with peripheral manifestations, five patients (7.2%) had type 1 arthritis (pauciarticular) and one patient (1.4%) had type 2 arthritis (polyarticular). A higher proportion of patients with CD had axial manifestations with or without peripheral manifestations (eight of 46; 17.4%) compared with patients with UC (10 of 81; 12.3%), but no difference was observed in patients with peripheral manifestations alone. Conclusions: Rheumatic manifestations in patients with IBD in Qatar are more prevalent than in other regions of the world. Peripheral manifestations were more prevalent than axial.